Pengaruh Motivasi dan Biaya Pendidikan Terhadap Minat Mahasiswa Akuntansi untuk Mengikuti PPAk - Ni’mah, Nazilatin; Mawardi, M. Cholid; Anwar, Siti Aminah (Universitas Islam Malang, 2024)
The purpose of this study is to analyze and examine the influence of motivation and cost of education on accounting students' interest in professional accounting education (PPAK). This study was conducted among. The investigation will last from October 2023 until completion. The research subjects are students of Unisma Accounting Department of FEB. Sampling was carried out using a purposive sampling method according to established criteria, and a total of 163 samples were collected. Research results show that both motivation and study costs significantly influence accounting students' interest in participating in PPAk. Motivation has a significant positive effect on the happiness of accounting students participating in PPA, and educational costs have a significant positive effect on the happiness of accounting students participating in PPAk.Keywords: Student Interest, motivation and education costs